The other side of sojourn : Tamil Muslim women’s oral history on late 20th century male migration - Banu, Fanzura (Nanyang Technological University, 2020)
How did male migration affect the lives of Tamil Muslim women in the late 20th century? For the first time, an exercise in historicizing the experiences of Tamil Muslim women through oral history interviews has been undertaken. 11 interviewees have shared their perception of change in gender norms between 1950 to 2000. This paper’s findings are that long term male migration did indeed provide opportunities for women to take up what were traditionally masculine roles when they were faced with absence of remittance or irregular communication. Otherwise, the extent of expansion in definitions of motherhood and wifehood has been limited due to restricted decision making and physical mobility especially for those who lived in joint family structures where they were cared for by other people. Additionally, research participants’ silences and framing of answers reveal persisting ideals of womanhood influenced by religion and family traditions.